2019
DOI: 10.1080/17430437.2019.1672152
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating female fitness doping: gender, identity and transgressions

Abstract: On the basis of qualitatively gathered interview material and data from various postings on a pro-doping online community called Flashback, the aim of this article is to describe and analyse how female users of performance and image enhancing drugs (PIED) understand and negotiate their use in relation to gender and the body. Positioned within post-structural feminism, the results show that there is an increasing amount of knowledge that not only targets but is also developed by and for women concerning PIED us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Gender designations and conceptualizations are in a constant process of being made, remade, and redefined. Explanations of how the body is socially molded and constructed, and how power relations are inscribed on the flesh, also suggest that the body can be seen as the starting point of a discussion about how to counteract and eventually change social representations, power structures, and dynamics (Andreasson & Johansson, 2021).…”
Section: Analytical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender designations and conceptualizations are in a constant process of being made, remade, and redefined. Explanations of how the body is socially molded and constructed, and how power relations are inscribed on the flesh, also suggest that the body can be seen as the starting point of a discussion about how to counteract and eventually change social representations, power structures, and dynamics (Andreasson & Johansson, 2021).…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Gender designations and conceptualizations are in a constant process of being made, remade, and redefined. Explanations of how the body is socially molded and constructed, and how power relations are inscribed on the flesh, also suggest that the body can be seen as the starting point of a discussion about how to counteract and eventually change social representations, power structures, and dynamics (Andreasson & Johansson, 2021). This line of thinking, which not only aims to dissect and analyze structures of oppression but also tries to work towards more utopian goals concerning women ´s emancipation and empowerment, is eminently present in the writings of many feminist scholars, such as Donna Haraway (1990), Judith Butler (1990), Sara Ahmed (2006), and others.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Participating in sports and leisure activities even becomes a promoter of social class mobility, thereby creating and accumulating social capital. The increasing amount of people partaking in sports and fitness activities has brought social and economic benefits, making it a thriving business (Chang, 2020;Andreasson and Johansson, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have demonstrated the importance of marketing to women and have begun to analyze the consumer behaviors of female consumers. Furthermore, researchers emphasize the particularity of women in the field of sports and leisure activities (Cuneen and Claussen, 1999;Chang, 2020;Andreasson and Johansson, 2021). To improve women's health, foster sports empowerment, and construct a friendly environment in which women can play sports and leisure activities, the Sports Administration of the Ministry of Education in Taiwan implemented the first and the world's second white paper on the promotion of women's sports in 2016 (Hsu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation